Влияние ионного безводородного азотирования на процесс наростообразования при обработке отверстий в чугунных деталях протяжками из быстрорежущих сталей - Студенец, С.Ф. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
In article problems of adhesive process at cutting broaching of orifices in details from grey irons by the tool strengthend on technology non hydrogen of ionic nitriding.The procedure and results of research of forces at turning grey pig-iron are submitted by the tool, to subjected nitriding in non hydrogen environment on different conditions. It is shown, as the change of nitriding conditions influences character of adhesive process.